1994
DOI: 10.1002/depr.3050020104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of early non‐response in depressed patients

Abstract: Many authorities recommend a 6-week trial of an antidepressant befire deciding whether the patient will have a favorable response. However, this length of time is fiequently impractical, especially f o r hospitalized patients. Some data suggests that ultimate response to a tricyclic antidepressant may be predicted fiom improvement within the first few weeks. To investigate this issue the authors analyzed data fiom six 6-week double-blind, controlled trials of selective serotonin reuptake inhibitors. Five studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In our earlier study (Katz et al, 1987), the clinical effects detected within the first 2 weeks were large and were predictive of eventual positive clinical outcome. Findings from a number of other studies (Small et al, 1981;Coryell et al, 1982;Khan et al, 1989;Nagayama et al, 1991;Stassen et al, 1993;Boyer and Feighner, 1994) have also confirmed the positive role of early clinical actions in predicting treatment outcome. The capacity to predict outcome early in treatment would not only shorten the length of a treatment trial but should also decrease morbidity and the risk of suicide from prolonged depressive symptoms (Kiloh et al, 1988).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In our earlier study (Katz et al, 1987), the clinical effects detected within the first 2 weeks were large and were predictive of eventual positive clinical outcome. Findings from a number of other studies (Small et al, 1981;Coryell et al, 1982;Khan et al, 1989;Nagayama et al, 1991;Stassen et al, 1993;Boyer and Feighner, 1994) have also confirmed the positive role of early clinical actions in predicting treatment outcome. The capacity to predict outcome early in treatment would not only shorten the length of a treatment trial but should also decrease morbidity and the risk of suicide from prolonged depressive symptoms (Kiloh et al, 1988).…”
Section: Introductionsupporting
confidence: 62%
“…There have been, however, a number of studies over the years (Small et al, 1981;Coryell et al, 1982;Katz et al, 1987;Khan et al, 1989;Nagayama et al, 1991;Boyer and Feighner, 1994) that have demonstrated a relationship between early response to ADs, mainly tricyclics, and treatment outcome. It is clear from the current study, however, that drug-specific types of behavioral responses in the first 1 or 2 weeks of treatment with DMI or paroxetine are highly predictive of later outcome.…”
Section: Prediction Of Drug Responsementioning
confidence: 99%
“…However, 70% of patients who were improved at day 10 were responders after 4 to 6 weeks of therapy (Stassen et al, 1994). Similar results have recently been reported by Boyer and Feighner (1994) in an analysis of paroxetine treatment of depression. Patients who did not respond after 3 weeks of treatment were unlikely to respond to further treatment.…”
Section: What Constitutes An Adequate Antidepressant Trial?supporting
confidence: 90%
“…In contrast, survival-analytical methods suggest that among responders, onset of action occurs in more than 70% of cases within the first two weeks of treatment, with an early onset of action being highly predictive of later response. (Angst and Stassen, personal communication; Stassen et al 1993Stassen et al , 1997Coryell et al 1982;Boyer and Feighner 1994).…”
Section: Onset and Speed Of Action Of Antidepressantsmentioning
confidence: 99%
“…In contrast, survival-analytical methods suggest that among responders, onset of action occurs in more than 70% of cases within the first two weeks of treatment, with an early onset of action being highly predictive of later response. (Angst and Stassen, personal communication;Stassen et al 1993Stassen et al , 1997Coryell et al 1982;Boyer and Feighner 1994).When a new drug designed to increase effectiveness and to act more rapidly is produced, the attempt to evaluate its efficacy and onset in one clinical trial is obviously complicated. Some new drugs have yielded evidence that they act more rapidly than the established ones.…”
mentioning
confidence: 99%